Analisis Spasial Tingkat Kesulitan Jalur Pendakian Menuju Puncak Gunung Rinjani: Studi Komparatif Antar Jalur - Dedin Mahyudita Media Rohman; Muhamad Rizal Al Faoziah; Ahmad Dailamy; Puti Mahira; Nur Ranti; Syarifah Kalsum Qurratul Uyun; Armandha Redo Pratama (Universitas Negeri Gorontalo, 2025)
The growth of adventure tourism in Indonesia has led to increased mountain climbing activity, including on Mount Rinjani, which features several official trails with varying terrain characteristics. The problem addressed in this study is the lack of spatial analysis that systematically compares the difficulty levels of these trails. This study aims to analyze and classify the difficulty level of hiking trails to the summit of Mount Rinjani based on spatial parameters, including trail length, slope gradient, elevation gain, and number of water sources. The research method used is descriptive quantitative with a composite scoring analysis derived from digital map data, elevation models, and field surveys. The results show that the Senaru and Timbanuh trails are classified as high difficulty due to significant elevation gain and steep slopes. The Torean trail is moderately difficult, with challenging terrain but abundant water sources. The Sembalun and connector trails have low difficulty due to gentler terrain despite limited access to water. This study concludes that a spatial approach provides objective information for assessing trail difficulty and serves as a foundation for planning safe and sustainable nature-based tourism